2021
DOI: 10.1155/2021/6632635
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postmastectomy Radiotherapy on Locoregional Control and Disease-Free Survival in Patients with Breast Cancer Treated with Neoadjuvant Chemotherapy

Abstract: Background. The impact of postmastectomy radiotherapy (PMRT) in patients receiving neoadjuvant chemotherapy (NAC) is unclear. The purpose of this study is to identify the patients who may benefit from PMRT. Methods. We retrospectively analysed patients with clinical stage II-III breast cancer who underwent NAC and modified radical mastectomy at our centre from 2007 to 2015. We investigated the relationship amongst locoregional recurrence rate (LRR), disease-free survival (DFS), and clinical pathological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…To further assess whether PMRT can benefit patients after NAC, the PubMed database was systematically searched for using the search terms, “postmastectomy radiation therapy”, “neoadjuvant chemotherapy” and “breast cancer”, for studies of PMRT after NAC published from March 1993 to November 2021. Of the 184 articles identified, nine ( 13 21 ) report results similar to ours ( Table 6 ). Eight of these studies reported the results of event-free survival analysis, such as locoregional recurrence (LRR), local recurrence free survival (LRFS), DFS, recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) ( 13 16 , 18 21 ), whereas six studies reported OS and cause-specific survival (CSS) rates ( 13 17 , 20 ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…To further assess whether PMRT can benefit patients after NAC, the PubMed database was systematically searched for using the search terms, “postmastectomy radiation therapy”, “neoadjuvant chemotherapy” and “breast cancer”, for studies of PMRT after NAC published from March 1993 to November 2021. Of the 184 articles identified, nine ( 13 21 ) report results similar to ours ( Table 6 ). Eight of these studies reported the results of event-free survival analysis, such as locoregional recurrence (LRR), local recurrence free survival (LRFS), DFS, recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) ( 13 16 , 18 21 ), whereas six studies reported OS and cause-specific survival (CSS) rates ( 13 17 , 20 ).…”
Section: Resultssupporting
confidence: 65%
“…Of the 184 articles identified, nine ( 13 21 ) report results similar to ours ( Table 6 ). Eight of these studies reported the results of event-free survival analysis, such as locoregional recurrence (LRR), local recurrence free survival (LRFS), DFS, recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) ( 13 16 , 18 21 ), whereas six studies reported OS and cause-specific survival (CSS) rates ( 13 17 , 20 ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The PubMed literature search resulted in 184 articles related to PMRT after NAC (from 1993 Mar to 2021 Nov), by using search terms "postmastectomy radiation therapy" "neoadjuvant chemotherapy" and "breast cancer" in all their forms. After reviewing the abstracts and full texts of all these literatures, nine studies [11][12][13][14][15][16][17][18][19] were found to report results comparable to our study. The summary of the literature search and a comparison of the nine studies to our results are presented in Table 6.…”
Section: Indications For Pmrt After Nac: Current Literature Reviewsupporting
confidence: 68%
“…It is needed to point out that, in their study, the locoregional recurrence or distant metastasis rate was with no difference between PMRT and non-PMRT group. The latest study by Zhang (2021) [19] of 554 clinical stage II-III patients, demonstrated that PMRT signi cantly reduced 5-years LRR in clinical stage II-III patients after NAC, however those with ypN 0 derived no local control or survival bene t from PMRT.…”
Section: Discussionmentioning
confidence: 99%